Cu-BTC / biomass carbon composite material and preparation method and application thereof
By combining freeze-drying and high-temperature activation with Cu-BTC co-synthesis, a Cu-BTC/biomass carbon composite material with high specific capacity and cyclic stability was prepared, which solved the problems of low specific capacity and poor stability of biomass materials in supercapacitors and realized the application of high-performance electrode materials.
Patent Information
- Application Number
- CN202510957212.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-10-03
AI Technical Summary
Biomass materials have low specific capacitance and poor cycle stability in supercapacitors, and existing technologies are difficult to effectively improve.
The Cu-BTC/biomass carbon composite material was prepared by freeze-drying biomass materials combined with ball milling and high-temperature activation methods. Through the co-synthesis of organic ligands and Cu salts, a porous structure was formed to improve the specific surface area and stability.
The prepared Cu-BTC/biomass carbon composite material exhibits high specific capacity and excellent cycling stability under high current load, and is suitable for supercapacitor electrode materials with the characteristics of environmental friendliness and low cost.
Smart Images

Figure CN120748934A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy materials, and specifically relates to a Cu-BTC / biomass carbon composite material and a preparation method and application thereof. Background Art
[0002] The disposal of solid waste and toxic and hazardous gases generated by the use of fossil fuels is a major issue worldwide. At the same time, the characteristics of fossil fuels as non-renewable energy can also cause serious energy crises. In recent years, renewable energy has begun to replace or supplement fossil fuels in some areas.
[0003] Biomass resources are abundant and widespread worldwide, offering a sustainable alternative to dwindling fossil fuels. Due to their renewable, cost-effective, and environmentally friendly nature, some biomass materials with little or no economic value, including rice husks, coconut shells, corn leaves, shrimp shells, and crab shells, have been successfully converted into high-value carbon-derived materials and are attracting widespread attention in the energy storage field.
[0004] There are many types of biomass, and the performance of the biochar prepared from them varies greatly due to differences in component content, component distribution, connection mode, inherent microstructure and chemical composition. Xu et al. (Walnut shell derived porous carbon for a symmetric all-solid-state supercapacitor [J]. Applied Surface Science, 2017, 411:170-176) used walnut shells to prepare activated carbon by hydrothermal treatment, and then activated it with potassium carbonate solution. At a current density of 0.5 A / g, the specific capacitance of the walnut shell derived carbon material was 255 F / g. Pan et al. (Preparation and Capacitive Properties of Cellulose Derived Porous Carbon, Journal of Normal University Science. 2023, 43(05)) used cellulose extracted from waste corn straw as raw material, and prepared biomass porous carbon material by combining pyrolysis and activation methods. It was applied to porous carbon material electrodes and the capacitance was 255 F / g at a current density of 0.3 A·g -1 When the specific capacitance is 210.74F·g -1 When the current density increases to 10 A·g -1 When the specific capacitance reaches 175.89 F·g -1 , the capacitor showed a capacitance retention of 82.69%.
[0005] Electrode materials, the core of supercapacitors, directly determine important electrochemical performance indicators such as capacitance and energy density. Carbon-based supercapacitors have attracted considerable attention due to their abundant reserves, strong conductivity, large specific surface area, easily tunable microstructure, and stable chemical structure. Although biochar has been used in supercapacitors, its specific capacitance and cycling stability still need to be improved.
[0006] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the Invention
[0007] The purpose of the present invention is to provide a Cu-BTC / biomass carbon composite material and its preparation method and application. The Cu-BTC / biomass carbon composite material of the present invention has extremely high specific capacity and excellent cycle stability and can be used in supercapacitors.
[0008] In order to achieve the above object, the present invention provides a method for preparing a Cu-BTC / biomass carbon composite material, which comprises: The biomass material is freeze-dried and then pre-carbonized at 500°C under an inert gas atmosphere to obtain a product T; the product T is mixed with an inorganic base, activated at a high temperature of 550°C under an inert gas atmosphere, and then washed and dried to obtain a product TA; an organic ligand and the product TA are dissolved in an organic solvent mixture to obtain a solution A; a Cu salt is dissolved in water to obtain a solution B; the solution A and the solution B are mixed, heated at 80°C, a precipitate is separated, washed, and dried to obtain the Cu-BTC / biomass carbon composite material.
[0009] Preferably, the biomass material comprises: at least one of water chestnut shell and lotus stem; or / and, the organic ligand comprises: 1, 3, 5-benzenetricarboxylic acid; or / and, the Cu salt comprises: Cu(NO3)2·3H2O; or / and, the mass of the product TA is 1% of the total mass of the organic ligand and the Cu salt.
[0010] Preferably, the molar ratio of Cu ions to 1,3,5-benzenetricarboxylic acid in the Cu salt is 2:1.
[0011] Preferably, the pre-carbonization is carried out at a heating rate of 3°C / min, heated to 500°C, and kept warm for 2 hours; or / and, the high-temperature activation is carried out at a heating rate of 3°C / min, heated to 550°C, and kept warm for 2 hours; or / and, after the high-temperature activation, the inorganic alkali in the sample is washed away with dilute hydrochloric acid, washed with water, and vacuum dried at 70°C; or / and, after the solution A and solution B are mixed, heated at 80°C for 24 hours; or / and, the precipitate is washed with N,N-dimethylformamide and vacuum dried at 120°C; or / and, the freeze-drying temperature is -80°C, and vacuum is applied.
[0012] Preferably, the inorganic base is selected from potassium hydroxide; or / and the mass ratio of the product T to the inorganic base is 1:2.
[0013] Preferably, the organic solvent mixture is a mixture of ethanol and N, N-dimethylformamide; or / and, the ratio of the mass of the organic ligand to the volume of the organic solvent mixture is 1 g: 32 mL; or / and, the volume ratio of the organic solvent mixture to water is 2: 1; or / and, the ratio of the mass of the Cu salt to the volume of water is 1 g: 8 mL.
[0014] More preferably, the volume ratio of the ethanol to N, N-dimethylformamide is 1:1.
[0015] The second object of the present invention is to provide a Cu-BTC / biomass carbon composite material obtained by the preparation method.
[0016] The third object of the present invention is to provide the application of the Cu-BTC / biomass carbon composite material in supercapacitor electrode materials.
[0017] A fourth object of the present invention is to provide a supercapacitor, wherein the electrode material comprises the Cu-BTC / biomass carbon composite material.
[0018] Preferably, the electrode material comprises: the Cu-BTC / biomass carbon composite material, acetylene black and polytetrafluoroethylene.
[0019] More preferably, the mass ratio of the Cu-BTC / biomass carbon composite material, acetylene black and polytetrafluoroethylene is 8:1:1.
[0020] The Cu-BTC / biomass carbon composite material of the present invention and its preparation method and application have the following advantages: (1) The Cu-BTC / biomass carbon composite material prepared by the present invention can be used as a source of electrode material for high-performance supercapacitors, avoiding the defects of low specific capacity of biomass materials and poor cycling stability of Cu-BTC. The biomass carbon material prepared by the present invention has advantages such as being porous. With Cu-BTC as the base material, its high specific surface area provides accessible active sites for ion storage, allowing ions to diffuse rapidly into the pores under high current loads. At the same time, the densely distributed porous structure of biomass carbon can alleviate the stress generated during the charge and discharge process, which is beneficial to increasing electrochemical stability. Moreover, the prepared material is environmentally friendly and low-cost.
[0021] (2) The Cu-BTC / biomass carbon composite material of the present invention has high specific capacity and high cycle stability. Tested by a three-electrode system, in a 3M potassium hydroxide electrolyte, when the current density is 5A / g, the TA@CB electrode has a specific capacity of 13222F / g; when the current density is 50A / g, the TA@CB electrode still has a specific capacity of 12396F / g, and the material exhibits excellent rate performance. At a high current density of 30A / g, the specific capacity retention rate of the TA@CB electrode after 30,000 charge and discharge cycles reached 92.7%, demonstrating its excellent cycle stability;
[0022] (3) The present invention uses water chestnut shell biomass materials, which have higher specific capacity and excellent cycle stability compared with lotus stem biomass materials, and have great application prospects as electrode materials for supercapacitors; (4) The present invention pre-treats biomass by freeze-drying, which can prevent structural collapse or shrinkage caused by water evaporation, retain the original shape and internal pores, and make the internal structure of biochar more stable, able to withstand external pressure or chemical reactions without deformation. In addition, this treatment method can form abundant and evenly distributed pores in biochar, which helps to improve the electrochemical properties of the material. Compared with other drying technologies, freeze-drying has lower energy consumption, which helps to reduce energy consumption and costs in the production process. (5) The present invention performs ball milling on the pre-carbonized product T, which can refine the water chestnut carbon particles and make the composition uniform, which is beneficial to the subsequent high-temperature activation process of potassium hydroxide. In addition, the ball milling technology is economical and has strong scalability, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the X-ray diffraction pattern of the TA@CB composite material prepared in Example 1 of the present invention.
[0024] Figure 2Nitrogen adsorption-desorption isotherms and BJM pore size distribution diagrams of the TA@CB composite material prepared in Example 1 of the present invention and T, TA, Cu-BTC, T@CB, and TA@CB; in the figure, CB represents Cu-BTC; (a) is the nitrogen adsorption-desorption isotherms of T, TA, and CB; (b) is the nitrogen adsorption-desorption isotherms of T@CB and TA@CB; (c) is the BJM pore size distribution diagram of T, TA, and CB; (d) is the BJM pore size distribution diagram of T@CB and TA@CB.
[0025] Figure 3 The cyclic voltammetry curves of the TA@CB electrode prepared in Example 2 of the present invention at different scan rates of 1-10 mV / s are shown.
[0026] Figure 4 This is a constant current charge and discharge curve of the TA@CB electrode prepared in Example 2 of the present invention at different current densities of 5~50 A / g.
[0027] Figure 5 Graph showing the cycling performance of the TA@CB electrode prepared in Example 2 of the present invention and the LA@CB electrode prepared in Example 4 at a current density of 30 A / g. DETAILED DESCRIPTION
[0028] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0029] Note: If specific conditions are not specified in the examples, the experiments were conducted under conventional conditions or those recommended by the manufacturer. Instruments used without manufacturer information are commercially available. Raw materials and reagents used without manufacturer information are commercially available or can be prepared by known methods.
[0030] Throughout this disclosure, all features, such as values, amounts, amounts, and concentrations, specified in numerical ranges or percentage ranges are provided for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to encompass and specifically disclose all possible subranges and individual values within those ranges (including integers and fractions).
[0031] The features described in this disclosure may be combined in any manner, and as long as there are no conflicts between the combinations of these features, all possible combinations should be considered within the scope of this specification. Each feature disclosed in this specification may be replaced by any alternative feature that provides the same, equivalent, or similar purpose. Therefore, unless otherwise specified, the features disclosed are merely general examples of equivalent or similar features.
[0032] The present invention provides a Cu-BTC / biomass carbon composite material, its preparation method, and its application, which overcomes the drawbacks of low specific capacity and poor cycling stability of Cu-BTC biomass materials and successfully applies the material to high-performance supercapacitors. The present invention pre-treats the biomass material (such as water chestnut shells) through freeze-drying, preventing structural collapse or shrinkage caused by water evaporation while preserving the original morphology and internal pores. This makes the internal structure of the water chestnut carbon more stable, allowing it to withstand external pressure or chemical reactions without deformation. This treatment also creates abundant and evenly distributed pores within the biomass material (such as water chestnut shells), contributing to improved electrochemical performance. Compared with other drying techniques (such as forced air oven drying), freeze-drying consumes less energy, helping to reduce energy consumption and costs during the production process. It also avoids the damage to the porous structure that occurs with forced air oven drying. Furthermore, ball milling the pre-carbonized product T refines the biochar (water chestnut carbon) particles and achieves uniform composition, facilitating subsequent high-temperature activation with potassium hydroxide. Ball milling is economical, highly scalable, and suitable for large-scale production. The activated carbon product is activated at high temperature to obtain the final biomass carbon product, TA. This product is then co-synthesized with a Cu salt and an organic ligand to produce a Cu-BTC / biomass carbon composite material. The TA product does not affect the reaction between the Cu salt and the organic ligand. The resulting material is environmentally friendly and low-cost. Due to its high specific surface area and other advantages, it has extremely high specific capacity and excellent cycling stability, making it suitable for use in supercapacitors.
[0033] The Cu-BTC / biomass carbon composite material and its preparation method provided by the present invention have the following specific technical solutions: A method for preparing a Cu-BTC / biomass carbon composite material, comprising: The biomass material is freeze-dried and then pre-carbonized at 500°C under an inert gas atmosphere to obtain product T; the product T is mixed with an inorganic base, activated at a high temperature of 550°C, and then washed and dried to obtain product TA; the organic ligand and product TA are dissolved in an organic solvent mixture to obtain solution A; the Cu salt is dissolved in water to obtain solution B; solution A and solution B are mixed, heated at 80°C, the precipitate is separated, washed, and dried to obtain the Cu-BTC / biomass carbon composite material.
[0034] In a preferred embodiment of the present invention, the biomass material comprises at least one of water chestnut shells and lotus stems.
[0035] In a preferred embodiment of the present invention, the organic ligand comprises: 1, 3, 5-benzenetricarboxylic acid.
[0036] In a preferred embodiment of the present invention, the Cu salt comprises: Cu(NO3)2·3H2O.
[0037] In a preferred embodiment of the present invention, the mass of the product TA is 1% of the total mass of the organic ligand and the Cu salt.
[0038] In a preferred embodiment of the present invention, the molar ratio of Cu ions to 1,3,5-benzenetricarboxylic acid in the Cu salt is 2:1.
[0039] In a preferred embodiment of the present invention, the pre-carbonization conditions of the product T are heating in an inert gas atmosphere (such as a nitrogen atmosphere) using a tube furnace, with a heating rate of 3°C / min, heating to 500°C, and holding time of 2h.
[0040] In a preferred embodiment of the present invention, the high-temperature activation conditions of the product TA are heating in an inert gas atmosphere (such as a nitrogen atmosphere) using a tubular furnace, with the heating rate set at 3°C / min, heating to 550°C, and holding time for 2 hours.
[0041] In a preferred embodiment of the present invention, after the high-temperature activation, the inorganic alkali in the sample is washed away with dilute hydrochloric acid, and then washed with water, and dried in vacuo at 70°C.
[0042] In a preferred embodiment of the present invention, the solution A and the solution B are mixed and then heated at 80° C. for 24 hours.
[0043] In a preferred embodiment of the present invention, the precipitate is washed with N,N-dimethylformamide and dried at 120° C. in vacuum.
[0044] In a preferred embodiment of the present invention, the freeze-drying temperature is -80°C and vacuum is applied.
[0045] In a preferred embodiment of the present invention, the base is potassium hydroxide.
[0046] In a preferred embodiment of the present invention, the mass ratio of the product T to the inorganic base is 1:2.
[0047] In a preferred embodiment of the present invention, the organic solvent mixture is a mixture of ethanol and N,N-dimethylformamide, and more preferably, the volume ratio of ethanol to N,N-dimethylformamide is 1:1.
[0048] In a preferred embodiment of the present invention, the ratio of the mass of the organic ligand to the volume of the organic solvent mixture is 1 g: 32 mL.
[0049] In a preferred embodiment of the present invention, the ratio of the mass of the Cu salt to the volume of water is 1 g: 8 mL.
[0050] In a preferred embodiment of the present invention, the volume ratio of the organic solvent mixture to water is 2:1.
[0051] Unless otherwise specified, the technical solutions described in the present invention are all conventional solutions in the field, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0052] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0053] Example 1 A Cu-BTC / biomass carbon composite material, the preparation method of which comprises the following steps: (1) Fresh water chestnut shells were freeze-dried (cold trap temperature -80 °C, vacuum) until the sample was completely dry. Then, the sample was placed in a tube furnace and heated to 500 °C at a rate of 3 °C / min under a nitrogen atmosphere and maintained for 2 h to obtain a pre-carbonized product T. (2) The product T and potassium hydroxide were fully ground and mixed in a mass ratio of 1:2, and heated to 550°C at a rate of 3°C / min under a nitrogen atmosphere and maintained for 2 hours to obtain the activated carbon product TA; then the potassium hydroxide in the sample was washed away with 5% by mass dilute hydrochloric acid, and washed 6 times with deionized water, and dried in a vacuum oven at 70°C for 12 hours to obtain the final biomass carbon product TA; (3) Dissolve 1 g (0.004 mol) of copper nitrate trihydrate in 8 mL of water to obtain solution B; dissolve 0.5 g (0.002 mol) of 1,3,5-benzenetricarboxylic acid and the product TA (the mass of the product TA used is 1% of the total mass of copper nitrate trihydrate and 1,3,5-benzenetricarboxylic acid) in 16 mL of a mixed solution of ethanol and N,N-dimethylformamide in a volume ratio of 1:1 to obtain solution A; (4) The above solution A and solution B were mixed and ultrasonicated for 30 min. The mixed solution was then poured into a polytetrafluoroethylene-lined stainless steel autoclave, maintained at 80 °C for 24 h, and then naturally cooled. The precipitate was separated by centrifugation, washed with N,N-dimethylformamide 5 times, and dried in a vacuum oven at 120 °C for 20 h to obtain a TA@CB composite material.
[0054] Example 2 An electrode based on Cu-BTC / biomass carbon composite material, the preparation method of which comprises: 80 wt.% of the TA@CB composite material prepared in Example 1, 10 wt.% of acetylene black, and 10 wt.% of polytetrafluoroethylene were mixed uniformly in isopropanol. The resulting viscous mixture was rolled into a thin sheet, cut into small pieces, and finally pressed onto a nickel foam current collector to obtain a TA@CB electrode.
[0055] Example 3 A Cu-BTC / biomass carbon composite material was prepared using the same method as in Example 1, using lotus stems as the biomass material source, and was denoted as LA@CB.
[0056] Example 4 An electrode based on Cu-BTC / biomass carbon composite material was prepared from LA@CB using the same method as in Example 2.
[0057] Comparative Example 1 A T@CB composite material, the preparation method of which is basically the same as the method in Example 1, except that the pre-carbonized product T is directly subjected to step (3) to replace the product TA.
[0058] Experimental Example 1 Material Structure Characterization 1. X-ray diffraction pattern like Figure 1 The figure shows the X-ray diffraction pattern of the TA@CB composite material prepared in Example 1 of the present invention. Figure 1 It can be seen that the main diffraction peaks of TA@CB are located at 11.72°, 13.54°, 16.58°, 17.58°, 19.16°, 20.32°, 24.22°, 26.06°, 29.44°, 35.36° and 39.22°, corresponding to the (2 2 2), (4 0 0), (3 1 1), (5 1 1), (4 4 0), (6 0 0), (6 2 0), (7 3 1), (7 5 1), (7 7 3) and (8 8 2) crystal planes, respectively, which is consistent with the diffraction peak data of Cu-BTC, indicating that the coordination between copper ions and organic ligands is not affected by the addition of porous carbon during the synthesis process.
[0059] 2. Nitrogen-adsorption-desorption experiment like Figure 2 As shown in FIG, the nitrogen-adsorption-desorption isotherms and BJM pore size distribution diagrams of the TA@CB composite material prepared in Example 1 of the present invention and T, TA, Cu-BTC, T@CB and TA@CB. Figure 2 It can be seen that the specific surface area of CB is 518.8994m 2 / g, the average pore diameter is 2.3141 nm, and the specific surface area of T is 24.3536 m2 / g, the average pore diameter is 15.1928 nm, and the specific surface area of TA is 1042.6586 m 2 / g, the average pore diameter is 2.1917 nm, and the specific surface area of T@CB is 392.9729 m 2 / g, the average pore diameter is 2.5193 nm, and the specific surface area of TA@CB is 600.8646 m 2 / g, and the average pore diameter is 2.3633 nm. Compared with T@CB, the TA@CB electrode material of the present invention has a larger specific surface area and a slightly smaller pore size, which means more microporous structure, which can increase the density of active sites and the rapid transfer / diffusion of electrolyte ions.
[0060] Experimental Example 2 Electrochemical Performance Test A 3M potassium hydroxide solution was used as the electrolyte, and the TA@CB electrode prepared in Example 2 (or the LA@CB electrode prepared in Example 4), activated carbon, and mercury / mercuric oxide electrode were used as the working electrode, counter electrode, and reference electrode, respectively, to form a three-electrode system.
[0061] Cyclic voltammetry tests (CV, within the potential window of 0–0.8 V) were carried out on an electrochemical workstation (Shanghai CHI660D); constant current charge-discharge tests (GCD, within the potential window of 0–0.5 V) were carried out on a LAND CT2001A test system.
[0062] like Figure 3 As shown in FIG, the cyclic voltammetry curves of the TA@CB electrode prepared in Example 2 of the present invention at different scanning speeds of 1 to 10 mV / S are shown. Figure 3 It can be seen that the TA@CB electrode exhibits a typical highly reversible redox peak.
[0063] like Figure 4 As shown in FIG, the constant current charge and discharge curves of the TA@CB electrode prepared in Example 2 of the present invention at different current densities of 5 to 50 A / g are shown. Figure 4 It can be seen that the constant current charging curves of the TA@CB electrode all present a highly symmetrical triangle, indicating that it has excellent electrochemical reversibility and pseudocapacitive properties.
[0064] Furthermore, the TA@CB electrode of Example 1 exhibits an extremely high specific capacity. At a current density of 5 A / g, the TA@CB electrode has a specific capacity of 13222 F / g; at a current density of 50 A / g, the TA@CB electrode still has a specific capacity of 12396 F / g.
[0065] like Figure 5The figure shows the cycling performance of the TA@CB electrode prepared in Example 1 and the LA@CB electrode prepared in Example 4 at a current density of 30 A / g. Figure 5 It can be seen that at a high current density of 30 A / g, the TA@CB electrode maintained a specific capacity retention rate of 92.7% after 30,000 charge-discharge cycles, demonstrating its excellent cycle stability. However, the specific capacity of the LA@CB electrode decreased from 2620 F / g to 2140 F / g after 8,500 charge-discharge cycles, representing only 81.7% of the initial specific capacity. Compared with the TA@CB electrode, the LA@CB electrode has a lower specific capacity and poorer cycle stability.
[0066] In summary, the electrode material prepared by the present invention has high specific capacity and excellent cycle stability, and has great application prospects as an electrode material for supercapacitors.
[0067] Although the present invention has been described in detail through the above preferred embodiments, it should be understood that the above description is not intended to limit the present invention. After reading the above description, various modifications and substitutions of the present invention will become apparent to those skilled in the art. Therefore, the scope of protection of the present invention should be defined by the appended claims.
Claims
1. A method for preparing a Cu-BTC / biomass carbon composite material, characterized in that: The method includes: The biomass material was freeze-dried and then pre-carbonized at 500°C under an inert gas atmosphere to obtain product T; The product T is mixed with an inorganic base, activated at 550° C. under an inert gas atmosphere, and then washed and dried to obtain the product TA; Dissolving the organic ligand and the product TA in an organic solvent mixture to obtain solution A; Dissolve Cu salt in water to obtain solution B; The solution A and the solution B are mixed, heated at 80° C., the precipitate is separated, washed, and dried to obtain the Cu-BTC / biomass carbon composite material.
2. The preparation method according to claim 1, characterized in that The biomass material comprises: at least one of water chestnut shells and lotus stems; Or / and, the organic ligand comprises: 1, 3, 5-benzenetricarboxylic acid; Or / and, the Cu salt comprises: Cu(NO3)2·3H2O; Or / and, the mass of the product TA is 1% of the total mass of the organic ligand and the Cu salt.
3. The preparation method according to claim 2, characterized in that The molar ratio of Cu ions to 1,3,5-benzenetricarboxylic acid in the Cu salt is 2:
1.
4. The preparation method according to claim 1, characterized in that The pre-carbonization temperature was raised at a rate of 3°C / min to 500°C, and the holding time was 2h. or / and, the high temperature activation, heating rate is 3°C / min, heating to 550°C, holding time is 2h; or / and, after the high-temperature activation, washing the sample with dilute hydrochloric acid to remove the inorganic alkali, washing with water, and drying in vacuo at 70° C.; or / and, after mixing solution A and solution B, heating at 80° C. for 24 h; or / and, the precipitate is washed with N,N-dimethylformamide and dried in vacuo at 120° C.; Or / and, the freeze-drying temperature is -80°C and vacuum is applied.
5. The preparation method according to claim 1, characterized in that The inorganic base is selected from potassium hydroxide; Or / and, the mass ratio of the product T to the inorganic base is 1:
2.
6. The preparation method according to claim 1, characterized in that The organic solvent mixture is a mixture of ethanol and N, N-dimethylformamide; Or / and, the ratio of the mass of the organic ligand to the volume of the organic solvent mixture is 1g:32mL; Or / and, the volume ratio of the organic solvent mixture to water is 2:1; Or / and, the ratio of the mass of the Cu salt to the volume of water is 1g:8mL.
7. The preparation method according to claim 6, characterized in that The volume ratio of the ethanol to N, N-dimethylformamide is 1:
1.
8. The Cu-BTC / biomass carbon composite material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the Cu-BTC / biomass carbon composite material as claimed in claim 8 in supercapacitor electrode materials.
10. A supercapacitor, characterized in that: The electrode material comprises the Cu-BTC / biomass carbon composite material as claimed in claim 8.